The Environment is Life - Braslow, Juliet; Kalanga, Laibor; Muhogora, Focus (International Center for Tropical Agriculture, 2016)
This participatory video titled 'The Environment is Life' was filmed and produced by a group of 11 members from Mwangoi and Malindi villages Lushoto District, Tanzania. With this video, they want to communicate the message 'people should conserve and protect the environment so that they live a good and healthy life'. Through the film they demonstrate how they protect the environment, improve their yields, and the systems they use. Through a 6 day process facilitated by Juliet Braslow (CIAT), Katherine Snyder (CIAT), Laibor Kalanga (CIAT), and Focus Muhogora (SARI), the farmers learned video techniques, interviewing skills, and developed the story they wanted to share with their community, local leaders, and the world.